Analytic Network Process (ANP) Method: Factor Analysis of the Non-Implementation of Municipal Islamic Bonds in Sukuk Potential Areas in Indonesia - Mohammad Hatta Fahamsyah; Yos Soejarminto; Hamdan Ainul Yaqin; Adrianna Syariefur Rakhmat (East Asian Journal of Multidisciplinary Research, 2023)
This study seeks to examine the factors that have prevented the implementation of municipal Islamic bonds in a region with the potential for sukuk issuance in Indonesia. Previous research has identified regions with the potential to issue municipal Islamic bonds, yet none of these regions have done so thus far. Municipal Islamic bonds have the capacity to address regional budget deficits and finance the development of local infrastructure, thereby reducing the need for debt. Hence, the authors conducted research to identify the factors contributing to the lack of municipal Islamic bond issuance in these potentially sukuk regions in Indonesia. The analytic network process was employed as the methodology to determine the priority scale of causal factors. The findings indicate that two main problems exist, namely internal and external issues. The primary factor identified within the internal problem is human resources, while government regulation emerged as the primary factor within the external problem.